History, evolution and future perspectives of artificial insemination in domestic birds: Literature review (Research, Society and Development, 2023)
Artificial insemination (AI) is the most used reproduction biotechnique in domestic animal species. The use of this technique in poultry reproduction has enabled the rapid dissemination of genetic material from superior males to a large number of females. The first studies with AI in birds began more than a century ago with Ivanoff, in Russia, being considered a pioneer, after obtaining fertile eggs from chickens using semen collected from the vas deferens of roosters. Later, Burrows and Quinn developed the lumbosacral massage technique for semen collection, which is still used today. However, AI only took off from the moment the birds moved from extensive to intensive rearing systems, when they left the ground for suspended cages, mainly in laying hens, allowing greater control and optimization of inseminations. But it was from the 1950s that AI began to be used in commercial poultry, initially in Israel and Australia, followed by the United States and other countries such as Brazil. The technical-economic viability of using AI as a reproductive method in birds has already been proven by several works published in the national and international literature, in several species. In Brazil, despite AI technology in birds being little widespread, some activities have been developed in the experimental field and in the routine of poultry reproduction by private companies, private breeders “hobby” and some universities, but with an application well below that carried out for other species.